The Prevalence of Depression and Its Association With Quality of Life Among Pregnant and Postnatal Women in China: A Multicenter Study - Bo, Hai-Xin; Yang, Yuan; Zhang, Dong-Ying; Zhang, Meng; Wang, Pei-Hong; Liu, Xiao-Hua; Ge, Li-Na; Lin, Wen-Xuan; Xu, Yang; Zhang, Ya-Lan; Li, Feng-Juan; Xu, Xu-Juan; et al. (Frontiers in Psychiatry, 2021)
Background: This study examined the prevalence of depressive symptoms (depression hereafter) and its association with quality of life (QOL) among pregnant and postnatal women in China. Methods: In this multi-center, cross-sectional study, 1,060 pregnant and postnatal women from eight hospitals were assessed. Depression and QOL were measured using the Edinburgh Postnatal Depression Scale and the World Health Organization Quality of Life Questionnaire - brief version. Results: The prevalence of depression was 7.45% (95%CI: 5.87%-9.04%) in the sample. Women with depression had lower QOL in physical, psychological, social and environmental domains compared to those without. Women with physical comorbidities were more likely to suffer from depression (OR=2.391, 95%CI=1.384-4.130, P=0.002). Conclusion: Due to its negative association with QOL, increased attention should be paid to depression in pregnant and postnatal women. Regular screening assessment and preventive measures should be adopted to reduce risk of depression in this population.